Optimalisasi Manajemen Biaya Lingkungan untuk Efisiensi Operasional pada Perusahaan Manufaktur - Titania Intan Kartika; Dhea Putri Melati; Novya Sucy Wulandary; Dhivanadya Azzahra Putri (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines the role of environmental cost management in improving operational efficiency in manufacturing companies. Using a descriptive qualitative approach through a case study in Indonesia, the findings show that effective environmental cost management reduces waste and enhances production efficiency. Separate reporting of environmental costs also improves transparency and accountability.